2022
DOI: 10.3390/ijerph19126973
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Multi-Component Interventions on the Positive and Negative Aspects of Well-Being among Informal Caregivers of People with Dementia: A Systematic Review and Meta-Analysis

Abstract: The present review aims to examine whether multi-component interventions for informal caregivers of people with dementia are effective on positive and negative aspects of caregiver well-being. Eleven databases were searched from inception to 8 March 2021. Only randomized controlled trials reporting the effectiveness of multi-component intervention on positive and negative aspects of caregiver well-being were eligible. Endnote X7 (Thomson ResearchSoft, Stanford, CA, USA) was used for study selection and version… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 69 publications
0
9
0
1
Order By: Relevance
“…Informal caregivers (i.e., unpaid family members, friends or neighbors) play an essential role in dementia care, as they often organize and plan most, if not all activities of people living with dementia, including medical appointments and examinations, self‐care and daily living 51 . While these responsibilities can lead to caregiver burden with a significant impact on mental health and well‐being of informal caregivers, 51 numerous studies have demonstrated that multicomponent interventions targeting informal caregivers can improve their health 52 . The DemTab application offered a range of features designed to enhance communication and social participation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Informal caregivers (i.e., unpaid family members, friends or neighbors) play an essential role in dementia care, as they often organize and plan most, if not all activities of people living with dementia, including medical appointments and examinations, self‐care and daily living 51 . While these responsibilities can lead to caregiver burden with a significant impact on mental health and well‐being of informal caregivers, 51 numerous studies have demonstrated that multicomponent interventions targeting informal caregivers can improve their health 52 . The DemTab application offered a range of features designed to enhance communication and social participation.…”
Section: Discussionmentioning
confidence: 99%
“…51 While these responsibilities can lead to caregiver burden with a significant impact on mental health and well-being of informal caregivers, 51 numerous studies have demonstrated that multicomponent interventions targeting informal caregivers can improve their health. 52 The DemTab application offered a range of features designed to enhance communication and social participation. Although we employed numerous features specifically targeted Although some participating PCP used the DemTab application on a regular basis over the study period, overall, the general usage was low across PCP of the intervention group.…”
Section: Cochrane Review Of Tailored Interventions For Improving Clin...mentioning
confidence: 99%
“…To improve cognition, multidomain interventions should comprise at least three modalities, one of which is a cognitive approach [ 314 ]. Up to now, cognition and physical training is the most common combination of the multidomain approaches [ 314 , 379 , 381 , 382 ] whereby nutritional interventions and educational support play an important role in supporting and counseling PwAD and their families throughout the course of the disease [ 378 , 385 , 407 , 408 ]. The success of psychoeducational interventions depends on clear communication of theoretical contents and the active involvement of carers in practice sequences to implement new skills [ 303 , 385 ].…”
Section: Discussionmentioning
confidence: 99%
“…The absence of a meta-analysis of FA in science education is a major gap in the relevant research. Filling this void necessitates a thematic analysis of the relevant studies to discover common and distinct trends [18,19].…”
Section: Formative Assessment In Engineering Educationmentioning
confidence: 99%